EKSPRESI KENUSANTARAAN PADA BALAI ADAT SESAT AGUNG – TULANG BAWANG BARAT - Noor Adhitya Putri, Nadine; Astrina, Indri (Jurnal Riset Arsitektur, 2022)
Abstract - As a visual language, architectural expressions can be understood through arrangements of its elements with certain patterns or techniques. According to Rob Krier (1988), the assessment of geometric expressions cannot be separated from the composition of architectural forms, including proportion, rhythm, ornament, shape, material, color and texture. Along the way, Tulang Bawang Barat, which was later abbreviated as Tubaba, became a stopover for migrants from various regions. Regent Umar Ahmad pursued the construction of Tulang Bawang Barat by building a mosque and a convention hall to fill the empty fields in Tulang Bawang Barat. The architectural expression of Balai Adat Sesat Agung – with its modernity – considered as success in reproducing historical and cultural identity of Nusantaran architecture. In identifying the expressions of Nusantaran architecture, the analysis of Sesat Agung architecture is carried out in three areas: site, building, and structure. Through descriptive-analytical methods, this research begins by formulating the properties and compositions of Nusantaran architecture expressions forming through related theories, including Nusantaran architectural theory, concepts of properties and composition, and anatomy of architecture theory. Furthermore, the properties and composition of Sesat Agung are studied to identify the expressions of Nusantaran architecture which manifested in the architecture of the Balai Adat Sesat Agung. This study found that the architectural expression of the Sesat Agung has printed a new architectural identity in Tulang Bawang Regency. However, regardless of the form and the aesthetics it carries, one thing that is missing from Sesat Agung architecture is its spatial quality. Key Words: expression, Nusantaran architecture, Sesat Agung.